Analysis of Taxation Implementation in Construction Company (Case Study of PT DMK) - Satria, Adam Muhamad; Febriana, Hanin; Pradipta, Khairunissa Alika; Putri, Nurhanan Rachmi; Darwawi, Dela Rahmah; Irawan, Ferry (WIM Solusi Prima, 2024)
Taxes are income that taxpayers must pay to the state. The object of this research is PT DMK, which is engaged in construction services. Income from construction services will be subject to a final tax rate. This research aims to find out the application of taxation at PT DMK and the cases it has experienced. This research uses a qualitative method with primary data from interviews with the company and other supporting data such as the company's financial statements. This company uses tax regulations such as VAT, Income Tax 21, Income Tax 23, and Corporate Income Tax and has understood these tax provisions. Based on the interview results, PT DMK has implemented tax regulations properly in its company and stated that there has never been a problem in implementing corporate tax reporting to the state, such as delays in payment. However, there has been a case related to VAT, and the tax consultant who handled the problem has resolved the problem with the applicable tax provisions.